Methodology to analyze the degradation of structural timber in acidic atmospheres [póster y audio] - Paniagua Hernández, Viviana (2021)
The atmospheric composition varies according to geographic locations. In Costa Rica, part of the infrastructure is affected by corrosive atmospheres caused by volcanic activity and tropical climate humidity. The aim of this research is to propose a robust methodology to establish the influence of acid agents on the mechanical performance of structural Tectona grandis and Cupressus lusitanica specimens exposed to this environment. This research contemplates different acid pollution degrees and on-site and in laboratory analysis; Dynamic Elasticity Modulus Edyn, apparent Elastic Modulus Eapp, and chemical composition changes are the response variables. Among the highlighted results during the initial experimental stage, it was observed an estimated decline rate of 5-7% in Edy and 8-11% in Eapp, with a tendency of 3% more decrease in Cypress than in Teak. The acidic atmosphere remained between 0.5ppm and 1 ppm of SO2 gas concentration, and pH values of acid rain were 3.92±0.33 on average. In addition, specimens were sensitive to color change (∆E*>17) which can be considered for architecture design purposes. Since this environmental accelerates natural degradation, the proposed methodology seems suitable for monitoring wood degradation based on a six-month tracking study.